Geochemical characteristics of peat from two raised bogs of Germany; IOP Conference Series: Earth and Environmental Science; Vol. 48 : Environmental Observations, Modelling and Information Systems (ENVIROMIS-2016) - Mezhibor A. M. Antonina Mikhailovna (2016, 2016)
Title screen